Comparison of the rheological behavior of composite gels containing potato starch and enzyme-modified potato protein. (15th July 2022) - Zhu, Yu; Lu, Hongxia; Zhu, Zhijie; Li, Yuanyuan; Du, Xianfeng; Guo, Li
Abstract: Starch-protein interactions affect the rheological and textural properties of composite gels. The limitations of proteins as food ingredients can be overcome by enzyme modifications. Herein, to investigate the effect of enzyme-modified potato proteins on the properties of protein-starch composite gel food ingredients, we used laccase, peroxidase, or tyrosinase to catalyze the covalent cross-linking of potato protein (PP). Circular dichroism spectroscopy and gel electrophoresis indicated that the secondary structure of PP was altered after enzyme treatment. Laccase-treated PP (LPP) exhibited a stronger degree of cross-linking than peroxidase-treated PP (PPP) and tyrosinase-treated PP (TPP). Texture profile analysis confirmed that the composite gel of LPP and potato starch (LPP/PS) displayed a stable three-dimensional structure compared with PPP/PS, TPP/PS, or native PP/PS (control). Creep recovery of TPP/PS, PPP/PS, and LPP/PS (57.90, 81.77, and 92.08%, respectively) was increased vs. PP/PS (52.57%). The results provide a theoretical basis for improving the properties of potato-based composite gel. Highlights: The network of proteins was formed by laccase, peroxidase or tyrosinase. Enzyme resulted in a significant change of secondary structure of potato proteins. Laccase-treated potato protein had a stronger degree of cross-linking. Laccase-treated potato protein/potato starch gels had higher creep recovery. Laccase-treated potato protein/potato starch had stronger gel network.